Electrical stability of PLEDs - Kar Y.B.; Bradley D. (2023)
We report the impact of inserting a 10 nm thickness interlayer between the poly(3,4-ethylenedioxythiophene):poly(styrenesulphonate) (PEDOT:PSS) and light-emitting layers on degradation, in particular the electrical stability of the injecting electrodes, in encapsulated polymer light emitting diodes (PLEDs). Continuous electrical stress testing is carried out to study the time evolution of dark injection hole transients for devices with and without a poly [2,7-(9,9-di-n-octylfluorene)-alt-(1,4-phenylene-((4-secbutylphenyl)imino)-1, 4-phenylene)] (TFB) interlayer. A Sumitomo Chemical Company dibenzothiophene phenylenediamine copolymer (SC002) was used as light emitting layer and PLED characteristics with and without the interlayer are discussed together with lifetime data. 2010 IEEE.